2018
DOI: 10.18632/aging.101584
|View full text |Cite
|
Sign up to set email alerts
|

A single-nucleotide polymorphism (rs1805087) in the methionine synthase (METH) gene increases the risk of prostate cancer

Abstract: Methionine synthase (METH, i.e., MTR) is a key enzyme in the folate pathway, which plays a critical role in the synthesis, repair, and methylation of DNA. The association between METH gene polymorphisms and prostate cancer susceptibility remains ambiguous. Thus, we performed an updated meta-analysis of METH single-nucleotide polymorphism rs1805087 involving 12 independent case-control studies comprising 9986 prostate cancer patients and 40134 controls. The odds ratio and 95% confidence intervals were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…This polymorphism is the most common mutation of the METH gene and involves the A2756G substitution, which leads an aspartic acid to glycine transition at position 919 of the protein. Therefore, subjects carrying the METH G-allele might have an increased PCa risk (15,16). Another study reported that different SNPs are correlated with PCa predisposition; in particular, the variants rs7000448, rs1048169, rs2961144, rs4430796, rs12500426, rs2066827 and rs114798100 seem to correlate with PCa incidence (17).…”
Section: Susceptibility Polymorphismsmentioning
confidence: 99%
“…This polymorphism is the most common mutation of the METH gene and involves the A2756G substitution, which leads an aspartic acid to glycine transition at position 919 of the protein. Therefore, subjects carrying the METH G-allele might have an increased PCa risk (15,16). Another study reported that different SNPs are correlated with PCa predisposition; in particular, the variants rs7000448, rs1048169, rs2961144, rs4430796, rs12500426, rs2066827 and rs114798100 seem to correlate with PCa incidence (17).…”
Section: Susceptibility Polymorphismsmentioning
confidence: 99%
“…Moreover, the relevance of one carbon metabolism is also highlighted by the association between the levels of folate in peripheral blood, DNA methylation and colorectal tumor staging ( 61 ). Accordingly, the existence of polymorphisms and the increased expression or activity of enzymes participating in one-carbon metabolism are considered markers for highly proliferative and aggressive cancer phenotypes and chemoresistance ( 57 , 62 , 63 ).…”
Section: Cysteine As a Carbon Source In Cancermentioning
confidence: 99%
“…Интерес к генетическим вариантам генов, кодирующих ферменты фолатного цикла, связан с множеством публикаций, описывающих связь различных SNP с частотой самых различных заболеваний. Так, в литературе приведены публикации о связи SNP генов фолатного цикла с риском развития сосудистых заболеваний, онкологических заболеваний, акушерско-гинекологической патологии и бесплодия [16,17,[24][25][26][27][28][29][30][31].…”
unclassified